2014
DOI: 10.1371/journal.pone.0088017
|View full text |Cite
|
Sign up to set email alerts
|

Eucommia ulmoides Cortex, Geniposide and Aucubin Regulate Lipotoxicity through the Inhibition of Lysosomal BAX

Abstract: In this study we examined the inhibition of hepatic dyslipidemia by Eucommia ulmoides extract (EUE). Using a screening assay for BAX inhibition we determined that EUE regulates BAX-induced cell death. Among various cell death stimuli tested EUE regulated palmitate-induced cell death, which involves lysosomal BAX translocation. EUE rescued palmitate-induced inhibition of lysosomal V-ATPase, α-galactosidase, α-mannosidase, and acid phosphatase, and this effect was reversed by bafilomycin, a lysosomal V-ATPase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…By inhibition of NF- κ B signaling, aucubin prevents proinflammatory cytokine-induced inflammatory response [ 6 , 7 ]. Aucubin is also reported to regulate Bcl-2 family protein expression and inhibit cell death [ 12 ] and apoptosis [ 8 , 9 ]. Ho et al reported that aucubin protected against UVB-induced skin fibroblast activation by inhibition of the production of matrix metalloproteinase-1 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…By inhibition of NF- κ B signaling, aucubin prevents proinflammatory cytokine-induced inflammatory response [ 6 , 7 ]. Aucubin is also reported to regulate Bcl-2 family protein expression and inhibit cell death [ 12 ] and apoptosis [ 8 , 9 ]. Ho et al reported that aucubin protected against UVB-induced skin fibroblast activation by inhibition of the production of matrix metalloproteinase-1 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…plants Plantago lanceolata L. and Veronica officinalis L. (Plantaginaceae). Several pharmacological benefits have been reported for aucubin, such as hepatoprotective [7], anti-inflammatory [8], anti-oxidant [9,10], anti-osteoporosis [11], and neurotrophic effects [12,13]. Lv et al [14] reported that aucubin reduced the protein expression of α-SMA, collagen I, collagen III, and MMP-2, suppressed the generation of reactive oxygen species, and down-regulated the nicotinamide adenine dinucleotide phosphate-oxidase-4 mRNA expression in LX-2 cells.…”
Section: Aucubin Protects Against Tgfβ1-induced Cardiac Fibroblasts Amentioning
confidence: 99%
“…Citrus flavonoids have antioxidant, anti-inflammatory, and antitumor activities [2,16]. Hesperidin, a major compound of citrus peel [29], suppresses cell death through regulation of AMPK activation [30]. Along with other components in citrus peel, mTOR was inhibited by hesperidin.…”
Section: Discussionmentioning
confidence: 99%